Marketing the Hotel Sector in the Holy City of Najaf: An Analytical Study of the Design, Spaces, and Areas of Hotel Rooms (Czech Journal of Multidisciplinary Innovations, 2023)
The hotel sector is one of the most essential tourism sectors in developing or developed countries, as it contributes significantly to economic growth. Design by nature belongs to the plastic arts, and the art of creation is a comprehensive field that includes many specializations. Any design process needs a clear plan as well. Each type of design aims to achieve a specific function, and the study of architectural spaces, including the elements, foundations, and determinants they contain, is considered one of the most critical architectural studies, especially modern ones. It is a study that simulates man in an attempt to form an understandable language between man and the surroundings or the space he inhabits. The architectural space, with its physical composition, functional form, and aesthetic appearance, is the vessel in which humanity interacts to form civilization, which is considered the highest and finest creation of society, as the holy city of Najaf possesses distinct tourism components that make it It deserves to receive millions of tourists from all over the world, as it includes traces of multiple and ancient civilizations, enjoys a Mediterranean climate and provides essential infrastructure such as road and communications networks and trained tourism and hotel human resources, which constitutes a necessary base for the tourism industry and natural tourism recovery. Tourist hotels are one of the fundamental pillars on which tourism and hotel programs depend. The hospitality industry is considered the country’s cultural interface and the window through which tourists view the services and facilities provided for the stay and comfort of guests. They also represent a direct, practical translation of local culture regarding architectural style, construction style, interior design, and equipment— hotel, hospitality, communications, and transportation. From experience and comparison, foreign tourists notice that Najaf Al-Ashraf has the vast majority of tourist hotel services and buildings in Iraq that are not at the required level. In this research, we confirm that tourist hotel buildings equipped and designed on scientific foundations majorly in marketing the Iraqi tourism and hotel industry. From this standpoint, we focus on the primary service function in the hotel, which is the hotel room, in terms of studying and analyzing the interior design of the room (such as the spatial dimensions of the room, internal distribution and functional connectivity, color study, lighting, orientation and movement...etc.) and focuses on studying all elements of interior design ( Finishes, materials, colors used, furnishings, lighting elements, and technical services). The study confirms the relationship of the previous aspects of the interior design of the residence room to the environment (cultural, social, and surrounding climate).